Предмет: Алгебра, автор: morozko13373

помогите срочно пожалуйста​

Приложения:

Ответы

Автор ответа: sangers1959
1

Объяснение:

4)\ \\(\frac{c}{4})^{20}*(\frac{c}{4})^*=(\frac{c}{4})* (\frac{c}{4})^{25} \\(\frac{c}{4})^{20}*(\frac{c}{4})^*=(\frac{c}{4})^{25+1}  \\(\frac{c}{4})^{20}*(\frac{c}{4})^*=(\frac{c}{4})^{26} \\(\frac{c}{4})^*=(\frac{c}{4})^{26-20}\\(\frac{c}{4})^*=(\frac{c}{4})^{6}\\\ *=6.\\

6)\\(\frac{2}{5}y)^6*(\frac{2}{5}y)^*=(\frac{2}{5}y)*(\frac{2}{5}y)^8\\(\frac{2}{5}y)^6*(\frac{2}{5}y)^*=(\frac{2}{5}y)^{8+1} \\(\frac{2}{5}y)^6*(\frac{2}{5}y)^*=(\frac{2}{5}y)^{9}  \\ (\frac{2}{5}y)^*=(\frac{2}{5}y)^{9-6}\\  (\frac{2}{5}y)^*=(\frac{2}{5}y)^{3}\\\ *=3.

Похожие вопросы
Предмет: Русский язык, автор: Лизка1112